2004
DOI: 10.1124/mol.104.001321
|View full text |Cite
|
Sign up to set email alerts
|

Certain 1,4-Disubstituted Aromatic Piperidines and Piperazines with Extreme Selectivity for the Dopamine D4 Receptor Interact with a Common Receptor Microdomain

Abstract: We previously demonstrated that, in the D4 dopamine receptor, the aromatic microdomain that spans the interface of the second and third transmembrane segments influences the high-affinity interactions with the D4-selective ligand L750,667 [3-{[4-(4-iodophenyl) piperazin-1-yl]methyl}-1H-pyrrolo [2,3-b]pyridine] and the D2-selective ligands methylspiperone, aripiprazole, and its congener OPC4392 [7-[3-(4-(2,3-dimethylphenyl) et al., 2000). Here we tested a variety of 1,4-disubstituted aromatic piperidines/pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 39 publications
(43 reference statements)
4
66
0
Order By: Relevance
“…Second, it demonstrates how key molecular interactions between a ligand and a specific GPCR microdomain are influenced by occupancy of an allosteric site. In our case, the interactions that become accessible through the allosteric effect of sodium binding involve a -stack or T-type interaction between the ligand's aryl moiety and F2.61(91) of the receptor as we proposed previously (Kortagere et al, 2004). However, we found that in the D 2 -V2.61(91)F receptor, this favorable interaction can occur only if an interhelical -stack between the F2.61(91) and the adjacent F3.28(110), which forms a "hydrophobic brace," is disrupted.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Second, it demonstrates how key molecular interactions between a ligand and a specific GPCR microdomain are influenced by occupancy of an allosteric site. In our case, the interactions that become accessible through the allosteric effect of sodium binding involve a -stack or T-type interaction between the ligand's aryl moiety and F2.61(91) of the receptor as we proposed previously (Kortagere et al, 2004). However, we found that in the D 2 -V2.61(91)F receptor, this favorable interaction can occur only if an interhelical -stack between the F2.61(91) and the adjacent F3.28(110), which forms a "hydrophobic brace," is disrupted.…”
Section: Discussionmentioning
confidence: 91%
“…For all ligands tested within this structure class, the D 2 -V2.61(91)F mutant had affinities very similar to those measured for the wild-type D 2 receptor, including L-745,870 and six other D 4 -selective 1,4-DAPs (1.1-3.3-fold changes, Table 1). All of these 1,4-DAPs have been tested in previous binding studies designed to investigate molecular determinants of ligand selectivity for D 4 receptors versus D 2 receptor subtypes (Schetz et al, 2000;Kortagere et al, 2004), but only one of them (L-745,870 or CPPMA) had been tested on the D 2 -V2.61(91)F mutant, and it was reported to have a large improvement in binding affinity (Simpson et al, 1999).…”
Section: Ligand Docking Into D 2 Receptor Conformers From the M 19mentioning
confidence: 99%
See 2 more Smart Citations
“…For both structures, the linker is lined with Phe106, Val107, Tyr365, Thr369, and Thr373, in agreement with mutagenesis data on D3R or other dopamine receptors. 26 Both HM and X-ray structure explained very well the observed structure-activity relationships for D3R ligands. Briefly, an aromatic group is very important in the subcavity occupied by the phenyl of BP897.…”
mentioning
confidence: 72%